Conducting focus groups in neurodegenerative disease populations: ethical and methodological considerations. Issue 1 (13th January 2021) - Jones, Annabel; Morgan-Jones, Philippa; Busse, Monica; Shepherd, Victoria; Wood, Fiona
Abstract : Background: Involvement of vulnerable populations in research is critical to inform the generalisability of evidence-based medicine to all groups of the population. Objective: In this communication, we reflect on our previous research, and that of other authors, to identify and explore key ethical and methodological considerations. Discussion: Focus groups are a widely implemented qualitative methodology, but their use, particularly in vulnerable neurodegenerative disease populations, is not straightforward. Although the risk of harm is generally low in focus group research, neurodegenerative disease populations are particularly vulnerable to issues relating to comprehension and their capacity to consent. Physical and cognitive impairments may also affect social interactions among participants and therefore impact data collection and analyses. Conclusion: We offer a number of ethical and methodological recommendations to facilitate the processes of recruitment and data collection when conducting focus groups with neurodegenerative disease populations.